Fiscal and Monetary Policy Coordination, Macroeconomic Stability, and Sovereign Risk - Dennis Bonam; Jasper Lukkezen (Tinbergen Institute, 2014)
In standard macroeconomic models, debt sustainability and price level determinacy are achieved when fiscal policy avoids explosive debt and monetary policy controls inflation, irrespective of the relative strengths of each policy stance. We examine how these policy requirements for equilibrium stability and determinacy change in the presence of sovereign risk. An increase in sovereign risk reduces lender's willingness to hold government debt and raises consumption and inflation. Therefore, inflation and debt dynamics are determined jointly. To ensure stable macroeconomic conditions, both the fiscal and monetary stance must shift to offset debt sustainability concerns. We find that the adoption of a deficit target helps alleviate such concerns and raises the scope for macroeconomic stability.
Keywords: E52; E62; E63; 330; Fiscal and monetary policy coordination; equilibrium determinacy and stability; sovereign risk; policy rules